Case Report: Diabetes in Chinese Bloom Syndrome - Deng, Mingqun; Yu, Miao; Jiajue, Ruizhi; Feng, Kai; Xiao, Xinhua (Frontiers in Endocrinology, 2021)
Bloom syndrome (BS) is a rare autosomal recessive disorder that causes several endocrine abnormalities. So far, only one BS pedigree, without diabetes, has been reported in the Chinese population. We presented the first case of BS with diabetes in the Chinese population and explored the clinical spectrum associated with endocrine. Possible molecular mechanisms were also investigated. Our study indicated that BS may be one rare cause of diabetes in the Chinese population. We also found a new pathogenic sequence variant in BLM (BLM RecQ like helicase gene)(NM_000057.4) c.692T>G, which may expand the spectrum of BLM variants.